Crescimento incial de Joannesia princeps Vell. sob diferentes condições microclimáticas associadas à deficiência hídrica - Santos, Sanderléia de Oliveira dos (2014)
The objective of this research was to evaluate the influence of different microclimate conditions on the growth of seedlings Joannesia princeps Vell., in the establishment phase. The study was conducted in a greenhouse with controlled in multilaboratorial complex studies on climate change in tropical forests of the Department of Forestry and Wood Sciences Center of Agrarian Sciences, Federal University of Espírito Santo environment, located in the town of Jerome, ES (latitude 20°47'8"S, longitude 41°23'52"W and altitude 120 m) during the period from June 18 to September 12, 2013. Seedlings were used in the initial stage were transplanted to pots of 21,5 liter 30 cm deep, 37 cm top diameter and 27 cm bottom diameter. The experiment was conducted in four environments with different atmospheric demands, according to different combinations of values of temperature (°C) and Vapor Pressure Deficit - DPV (kPa), being called Lower temperature (20,9 ºC and 0.11 kPa) , Intermediate temperature (23,0 ºC and 0,53 kPa), Low Temperature Higher DPV (25,1 ºC and 0,92 kPa) and DPV Superior High Temperature (25,2 °C and 1,08 kPa), adopting three levels of soil water 90, 50 and 10% of the available water. Growth characteristics were analyzed by measuring height, diameter, leaf area and plant dry matter. To characterize the ecophysiological responses, readings of gas exchange, soil temperature and water potential were made. For growth characteristics, water potential and transmission of photosynthetically active radiation experimental design was completely randomized design (DIC) 3x4x12 factorial arrangement, with 3 levels of available water, 4 environments and 12 repetitions and ecophysiological responses and soil temperature factorial arrangement was 3x2x12, with 3 levels of water available, 2 rooms and 12 replications, the average, when significant, submitted to the Tukey test to compare the level of 5% probability. At the end of the experiment that lasted 86 days was observed that plants subjected to environments with higher temperature and low and high DPV had better outcomes compared to lower temperature and intermediate temperature environments. Based on these results, we conclude that the J. princeps had better development environments with higher temperatures with available soil water, in environments with mild temperatures. Regardless of whether or not there was drought the species was not sufficient development, with the occurrence of drought the DPV becomes important for the initial development of the species and the species have adapted well to forecast climate changes.